CFD simulation of the effect of an upstream building on the inter-unit dispersion in a multi-story building in two wind directions. Issue 150 (March 2016) - Cui, D.J.; Mak, C.M.; Kwok, K.C.S.; Ai, Z.T.
Abstract: Previous studies on inter-unit dispersion are limited to isolated buildings. The influence of an upstream interfering building may significantly modify the indoor airflow characteristics of the wind-induced natural ventilated downstream interfered building. Motivated by the findings in previous studies, namely that infectious respiratory aerosols exhausted from a unit can re-enter into another unit in the same building through building envelope openings, this study investigates the inter-unit pollutant dispersion around a multi-story building in two wind directions by employing the computational fluid dynamics (CFD) method. The CFD model employed in this study has been validated against previous experimental data. The results show that the presence of an upstream building greatly changes the path lines around the downstream target building and the pollutant transportation routes around it. The presence of a low upstream building also greatly increases the average air exchange rate (ACH) values and the pollutant re-entry ratios ( R k ) below the source unit on the windward side of the downstream target building for normal wind incidence. However, the presence of a high upstream building greatly increases the average ACH values on the windward side and increases the R k on the leeward side of the downstream building for oblique wind incidence. Highlights: Interunit pollutant dispersion in a naturally ventilated building was investigated. Effect of an upstream interfering building on the target building was examined. A high and a low upstream buildings were considered. An upstream building improves ventilation performance of the target building. An upstream building enhances Interunit dispersion in the target building.